The Translation Procedure of Pyschological Terms in the Interpretation of Dream into Indonesian in Tafsir Mimpi - Ririn Tasumbey (Jurnal Pendidikan dan Sastra Inggris, 2023)
Translation is a process of transfering meaning from source language to target language. As every language in this world are different, translation hold a very important role for universe. There are number of fields which are related to the translation works such as economic text, law text, religion text and also psychology text. Psychology is really necessary for mankind as it is connected to the human‟s behavior. The focus of the study is the psychological terms which is gotten from the book entitled The Interpretation Of Dreams and it‟s translation on the book entitled Tafsir Mimpi. The original book The Interpretation Of Dreams is writen by Sigmund Freud in 1900 and the translation book is translated by H. Supriyanto Abdullah (2015). In conducting this research, there are few theories will be applied such as translation procedures which is purposed by Vinay and Darbelnet (1959) and also Hatim and Munday (2004) which is about the ideology of translation. This study is qualitative research which will be supported by quantitave research when determine the ideology of translation. Product of the translation is the main focus of this research. Vinay and Darbelnet (1959) stated that there are seven procedures of translation. They are calque, literal, borrowing, transposition, modulation, equivalence and adaptation. Borrowing is divided into three kinds; pure borrowing, naturalization borrowing, and cultural borrowing. Apart from the procedures of translation, the ideology will also be analyzed. According to Hatim and Munday (2004), there are two types of translation ideology. They are domestication which is oriented to the target language text and another one is foreignization which is oriented to the souce language text.